A 5,000-Year Fire History in the Strait of Georgia Lowlands, British Columbia, Canada - Murphy, Sinead F.; Pellatt, Marlow G.; Kohfeld, Karen E. (Frontiers in Ecology and Evolution, 2019)
Improved knowledge of long-term fire regimes and climate-fire-human relationships are important for effective management of forested ecosystems. In this study, we use two, high-resolution sedimentary-charcoal records to provide new, mid to late Holocene fire histories for the driest forests in south coastal British Columbia, Canada: Somenos Lake in the Moist Maritime Coastal Douglas Fir (CDFmm) forests on southeastern Vancouver Island and Chadsey Lake in the Dry Maritime Coastal Western Hemlock (CWHdm) forests in the central Fraser Valley. Peak fire frequency at Somenos Lake in southeast Vancouver Island was highest prior to 3500 cal yr BP at 9.5 fires per 1000 years (at 4500 cal yr BP), with a mean fire return interval of 188 years (122-259) and 24 fire peaks for the 4855 year record. Peak fire frequency at Chadsey Lake in the Fraser Valley of the Lower Mainland of BC was highest (5.9) at 2736 cal yr BP but fairly uniform from 4300 to 2500 cal yr BP. The mean fire return interval at Chadsey Lake was 214 years (150-285) with 15 fire peaks for the 4200 year record. The fire history for Chadsey Lake appears to be strongly tied to broad regional climate patterns for the region whereas the variability in the Somenos Lake fire record displays a more complex pattern likely the result of the interplay between climatic and anthropogenic factors. Our results show how different age models using long- vs short-term temporal scales of analysis can affect fire history interpretation and highlight the importance of considering spatial variability when interpreting mechanisms driving fire activity in this region.